The Aristotelian Mirabilia and early Peripatetic natural science
1 online resource.
Keywords: "This is the first volume devoted to the sections of the Aristotelian Mirabilia on natural science, filling a significant gap in the history of the Aristotelian study of nature and especially of animals. The chapters in this volume explore the Mirabilia, or De mirabilibus auscultationibus (On Marvelous Things Heard), and its engagement with the natural sciences. The first two chapters deliver an introduction to this work: one a discussion of the history of the text; the other a discussion of Aristotelian epistemology and methodology, and the role of the Mirabilia in that context. This is followed by eight chapters that, together, are effectively a commentary on those sections of the Mirabilia with close connections to Aristotle's Historia animalium and to a number of Theophrastus' scientific treatises. Finally, the volume ends with two chapters on thematic topics connected to natural science running throughout the work, namely color and disease. The Aristotelian Mirabilia and Early Peripatetic Natural Science should prove invaluable to scholars and students interested in the ancient Greek study of nature, ancient philosophy, and Aristotelian science in particular"--